Corrosion of 304 stainless steel in static liquid lithium under high vacuum. (December 2020) - Meng, X.C.; Huang, M.; Li, C.L.; Xu, W.; Sun, Z.; Qian, Y.Z.; Li, L.; Yuan, X.L.; Huang, J.J.; Gao, X.; Li, J.G.; Zuo, G.Z.; et al.
Highlights: Corrosion behaviors of 304SS exposed to liquid Li at 700 K for 1320 h under high vacuum were investigated. Corrosion of 304 SS in liquid Li at 700 K was compared to at 600 K and 640 K. Cu of sealing gasket was deposited on the wall of test vessel. Abstract: To study the compatibility especially the corrosion characteristic of structural material stainless steel (SS) with liquid lithium (Li) is an important factor for the simultaneous application of liquid Li and SS as a blanket material or potential plasma facing material (PFM) in future fusion devices. The corrosion behaviors of 304SS exposed to liquid Li at 700 K for 1320 hr under high vacuum were investigated. After exposure to liquid Li, 304SS produces non-uniform corrosion which includes corrosion products and grain boundary corrosion. Compared with the corrosion behaviors at 600 K and 640 K, temperature plays an important role in the corrosion behaviors of 304SS in static liquid Li. The weight loss, corrosion depth and corrosion products of 304SS specimens increase with the corrosion temperature. In general, the compatibility between 304SS and static liquid Li is relatively good under the experimental conditions. And besides, it is unexpectedly found that the compatibility of copper with Li is not good.